Leitura literária de saudade da vila : lei 10.639/03 em sala de aula - Gomes, Maiane Moura (2016)
This dissertation named “Leitura literária de Saudade da Vila: Lei 10.639/03 in classroom” presents a work proposal for the final years of Elementary School, through the reading of a literary work for children which focuses on social issues. This research aims to develop a literay reading proposal that closes the book and the reader, in order to guarantee that Literature has more space in the classroom and, through this, the students at 6th grade in a public school in Bahia, have a conscious and reflective reading formation. Therefore, we use the concepts of reading, literary reading, literary literacy, model reader, recepcional method, basic sequence, children and youth literature, afro-Brazilian literature, racism at school, character under the perspective of Jouve (2002), Cosson (2010, 2011), Cruz (2012), Franco (2011), Eco (1986), Bordini e Aguiar (1988), Zilberman (2003, 2009), Filipouski (2012), Coelho (1991), Turchi (2006), Costa (2002), Silva (1995), Munanga (2005), Gomes (2016), Rodrigues (2011), Duarte (2008), Brait (1985), Candido (2007), Rosenfeld (2007), Cavalleiro (2007), among others. Besides, we also use The National Curriculum Standards (1988), National Curriculum Guidelines for Education and Ethnic-racial Relationships and for the Afro-Brazilian History and Culture and Law 10.639/03. In order to achieve the goals of this work, we have elaborated a sequence of activities, based on the receptional method and on the basic sequence, that has explored the literary work Saudade da Vila, by Luiz Galdino. The sequence was divided in four moments: talk early, introduction, reading and interpretation, which has facilitated the proposal aplication and the involvment of students. This research has adopted as metodological tool the research-action approach. Because of this choice, in all the steps of the work, we have searched to involve the students and enhance the literary reading to discuss the ethnic-racial issues. We have divide this dissertation into the sections of theoretical foundation, metodology and data analysis. We hope, therefore, that the experience with literary reading developed in this work can motivate other teachers and contribute to challenge of forming good readers.